2023
DOI: 10.4236/ape.2023.131006
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Tromso Social Intelligence Scale (TSIS)

Abstract: Objective: Develop and test the psychometric properties of an Arabic-language version of Tromso Social Intelligence Scale (TSIS). Method: A total of 807 physical education students at Kef-Higher Tunisia's Institute of Physical Education and Sports with Mean age were 21.43 ± 1.79 participated in this study. Females (n = 414) outnumbered men (n = 397). Subjects were divided into exploratory and confirmatory groups and completed an adapted version of the Tromso Social Intelligence Scale (TSIS). Results: Principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Using this three-dimensional structure for SI, Silvera et al (2001) developed the Tromso Social Intelligence Scale, which includes social information processing, social skills, and social awareness, and was later widely accepted and used by other researchers (e.g., Grieve & Mahar, 2013;Gini, 2006;Yahyazadeh-Jeloudar & Lotfi-Goodarzi, 2012;Ebrahimpoor et al, 2013;Rostamian & Sadrabadi, 2016). This tool, which defines SI with three dimensions, has demonstrated strong psychometric properties and has been implemented in numerous countries with high validity and reliability scores (Chater et al, 2023;Doğan & Çetin, 2009;Rezaie, 2011;Gini, 2006;Grieve & Mahar, 2013;Park et al, 2019). The superiority of the TSIS based on these three dimensions over other measures lies in the reduction of dimensions to three, compared to the more complex previous measures.…”
Section: Social Intelligencementioning
confidence: 99%
“…Using this three-dimensional structure for SI, Silvera et al (2001) developed the Tromso Social Intelligence Scale, which includes social information processing, social skills, and social awareness, and was later widely accepted and used by other researchers (e.g., Grieve & Mahar, 2013;Gini, 2006;Yahyazadeh-Jeloudar & Lotfi-Goodarzi, 2012;Ebrahimpoor et al, 2013;Rostamian & Sadrabadi, 2016). This tool, which defines SI with three dimensions, has demonstrated strong psychometric properties and has been implemented in numerous countries with high validity and reliability scores (Chater et al, 2023;Doğan & Çetin, 2009;Rezaie, 2011;Gini, 2006;Grieve & Mahar, 2013;Park et al, 2019). The superiority of the TSIS based on these three dimensions over other measures lies in the reduction of dimensions to three, compared to the more complex previous measures.…”
Section: Social Intelligencementioning
confidence: 99%
“…However, both social skills (x̄ =4.43, SD=0.831) and social awareness (x̄ =4.29, SD=0.963) fall within a neutral range and are perceived to be average, with room for improvement. This indicates that university students have minimal capacity to recognize, comprehend, and address the needs of others (Goleman, 1995;Hubbard, 2021) and thereof, have neither high nor low ability to behave in a way that is appropriate for the time, location, and circumstances (Chater et al, 2023).…”
Section: Social Intelligence Of the University Studentsmentioning
confidence: 99%
“…In addition, Goleman (1995) defined social awareness as the capacity to recognize, comprehend, and address the needs of others (Hubbard, 2021). Chater et al (2023) further identified social awareness as the individual's ability to behave in a way that is appropriate for the time, location, and circumstances. Social awareness has been linked to improved resilience and the ability to create profound relationships, both of which may reduce negative consequences in later life (Dennis, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weis and Süß (2007) supported the multidimensional structure of social intelligence for the domains of social knowledge, social understanding, and social memory. The Tromso social intelligence scale contains three different components: social information processing, social awareness, and social skills created ) and adopted by different countries (Chater et al, 2023;Sook Kyoung et al, 2019, Zulkifli et al, 2021. The Social Information Processing Model consists of social and behavioral adaptation of children in line with their responses to the social situations they encounter.…”
Section: Introductionmentioning
confidence: 99%